Positive expectations predict improved mental-health outcomes linked to psychedelic microdosing - L. S. Kaertner (Nature Portfolio, 2021)
Abstract Psychedelic microdosing describes the ingestion of near-threshold perceptible doses of classic psychedelic substances. Anecdotal reports and observational studies suggest that microdosing may promote positive mood and well-being, but recent placebo-controlled studies failed to find compelling evidence for this. The present study collected web-based mental health and related data using a prospective (before, during and after) design. Individuals planning a weekly microdosing regimen completed surveys at strategic timepoints, spanning a core four-week test period. Eighty-one participants completed the primary study endpoint. Results revealed increased self-reported psychological well-being, emotional stability and reductions in state anxiety and depressive symptoms at the four-week primary endpoint, plus increases in psychological resilience, social connectedness, agreeableness, nature relatedness and aspects of psychological flexibility. However, positive expectancy scores at baseline predicted subsequent improvements in well-being, suggestive of a significant placebo response. This study highlights a role for positive expectancy in predicting positive outcomes following psychedelic microdosing and cautions against zealous inferences on its putative therapeutic value.